Interest rate dynamics: An examination of mainstream and Keynesian empirical studies - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2024)
This paper critically reviews both mainstream and Keynesian empirical studies of interest rate dynamics. It assesses the key findings of a selected number of these studies, surveying the debates between the mainstream and the Keynesian schools. It also explores the debates on interest rate dynamics within the Post Keynesian school of thought. Lastly, the paper identifies the critical questions relevant for future empirical research.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Dynamics; Empirical Modeling of Interest Rates; Mainstream Economics; Keynesian Economics